Evaluation of educational experiences in times of COVID-19 an opportunity to innovate; case of students of the Universidad Técnica Nacional Sede Guanacaste - Loáiciga Gutiérrez, Jorge Luis (2021)
The objective of this study was to assess the impact of the methodological change of the teaching-learning process, from face-to-face to remote mode with the help of information and communication technologies (ICT) as a result of Covid-19, on students of the National Technical University (UTN). The work was developed according to a mixed descriptive and interpretative approach. The sample consisted of 117 UTN students based in the province of Guanacaste, Costa Rica. The results reveal opportunities for improvement in a convergent point such as connectivity and access to adequate devices to contemplate a remote modality with the use of digital tools under equal conditions. It is concluded that the research allows characterizing the institutional situation and are inputs for decision making.